2014
DOI: 10.1002/ange.201403353
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Site Platinum CO Oxidation Catalyst in Zeolite KLTL: Microscopic and Spectroscopic Determination of the Locations of the Platinum Atoms

Abstract: A stable site-isolated mononuclear platinum catalyst with a well-defined structure is presented. Platinum complexes supported in zeolite KLTL were synthesized from [Pt(NH 3 ) 4 ]-(NO 3 ) 2 , oxidized at 633 K, and used to catalyze CO oxidation. IR and X-ray absorption spectra and electron micrographs determine the structures and locations of the platinum complexes in the zeolite pores, demonstrate the platinumsupport bonding, and show that the platinum remained site isolated after oxidation and catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 23 publications
(34 reference statements)
1
48
0
Order By: Relevance
“…Furthermore, it has been reported that Pt single atoms within a zeolite can catalyze CO oxidation at 150 °C with moderate activity. 75 Unfortunately, no direct activity comparison between single Pt atoms and Pt clusters or nanoparticles was performed in that work.…”
Section: Catalytic Applications Of Supported Single Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that Pt single atoms within a zeolite can catalyze CO oxidation at 150 °C with moderate activity. 75 Unfortunately, no direct activity comparison between single Pt atoms and Pt clusters or nanoparticles was performed in that work.…”
Section: Catalytic Applications Of Supported Single Atomsmentioning
confidence: 99%
“…Thus, considering all previous reports on Pt single-atom catalysts, it seems that there are some contradictive conclusions on the active sites for Pt-catalyzed CO oxidation reaction. 72 , 73 , 75 , 78 However, it should be considered that the evolution of single atoms under reaction conditions is an important issue to be considered, and, so far, there is still not a clear global picture on the stability of single Pt atoms under reaction conditions, especially for those catalysts working at higher temperature (>90 °C).…”
Section: Comparison Of the Catalytic Behavior Of Single Atoms Nanoclmentioning
confidence: 99%
“…Spatial confinement is considered to be another effective method to synthesize SACs in which the separation and encapsulation of suitable mononuclear metal precursors with porous materials can prevent the agglomeration of single atoms. Based on this, several different carbon porous materials including zeolite [46,47], MOFs [48][49][50] and covalentorganic frameworks [51][52][53] have been used as templates for [38]. Copyright 2013, Nature Publishing Group.…”
Section: Mof-derived Single-atom Catalystsmentioning
confidence: 99%
“…These methods, however, still face a few challenging problems for practical applications, such as the complicated equipment, high-cost metal precursors used for synthesis, and very low metal loading. Another efficient strategy toward atomically dispersed catalysts is to use high–surface area supports that can supply numerous anchor sites for fixing large-content metal atoms, typically including metal oxide nanoparticles ( 4 , 5 ), zeolite ( 19 ), mesoporous graphitic carbon nitride ( 20 ), covalent triazine frameworks ( 21 ), and surface-functionalized porous carbons ( 22 ). In particular, Zeng and co-workers achieved a very high loading of 7.5 wt % for atomically dispersed Pt supported on monolayered MoS 2 ( 23 ); Kim and co-workers reported a 5 wt % atomically dispersed Pt on a microporous sulfur-doped carbon (micro_S-C) support that was prepared by templating zeolite and using toxic H 2 S gas as sulfur source ( 12 ).…”
Section: Introductionmentioning
confidence: 99%